Efektivitas dan Dampak Program SIMANTRI terhadap Pendapatan dan Kesempatan Kerja Rumah Tangga Petani di Kecamatan Nusa Penida Kabupaten Klungkung - Bhuanaputra, Kadek Widiandita; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 5, Mei 2017 (pp. 677 - 919), 2017)
Agricultural sector in Bali Province tends to decrease due to the rapid growth in the tertiary sector that is accommodation food and drink. The agricultural sector is still needed in order to maintain food security and land and support the tertiary sector in the unfinished materials providers, on the other hand tend to be identical with poverty agriculture. In order to reduce the level of poverty of farm households, the Bali provincial government launched a program of integrated agriculture system that is expected to improve the living standards of farmers become better, but the implementation is still a problem, that the program in the district of Nusa Penida SIMANTRI not go well as expected. The purpose of this study was to determine the level of program effectiveness SIMANTRI seen from indicators of input, process and output, and determine the impact SIMANTRI program on incomes and employment opportunities of farm households in the district of Nusa Penida. This research was conducted in Klungkung includes 17 Gapoktan in Nusa Penida. Object of the study include the effectiveness Simantri program, income, and employment. Samples in this study amounted to 78 respondents. The method used in this study include observation, structured interviews, and in-depth interviews. This research using descriptive statistical tests to see the trends the perception of respondents and inferential statistical tests, which Wilcoxon test to analyze the impact of the Program SIMANTRI on incomes and employment opportunities of farm households. Based on the results obtained the conclusion that the level of program effectiveness Simantri in the district of Nusa Penida, Klungkung regency is quite effective and Simantri program and a significant positive impact on the income and employment of farm households in the district of Nusa Penida, Klungkung regency.
Keywords: program simantri, efektivitas, pendapatan, kesempatan kerja